Studies in the History of the Exact Sciences in Honour of David Pingree - Burnett, Charles,; Hogendijk, Jan P.,; Plofker, Kim,; Yano, Michio, (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
This collection of essays reflects the wide range of David Pingree's expertise in the scientific texts (above all, concerning astronomy and astrology) of Ancient Mesopotamia, Greece, India, Persia, and the medieval Arabic, Hebrew and Latin traditions. Both theoretical aspects and the practical applications of the exact sciences-in time keeping, prediction of the future, and the operation of magic-are dealt with. The book includes several critical editions and translations of hitherto unknown or understudied texts, and a particular emphasis is on the diffusion of scientific learning from one culture to another, and through time. Above all, the essays show the variety and sophistication of the exact sciences in non-Western societies in pre-modern times.